2022
DOI: 10.1152/jn.00541.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cross-frequency phase-amplitude coupling in repetitive movements in patients with Parkinson’s disease

Abstract: Bradykinesia is a cardinal motor symptom in Parkinson's disease (PD), the pathophysiology of which is not fully understood. We analyzed the role of cross-frequency coupling of oscillatory cortical activity in motor impairment in PD patients and healthy controls. High-density EEG signals were recorded during various motor activities and at rest. Patients performed a repetitive finger pressing task normally, but were slower than controls during tapping. Phase-amplitude coupling (PAC) between β (13-30Hz) and broa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…It was found that phase-amplitude coupling (PAC) between the theta and high-gamma frequencies was impaired in awake and in non-REM sleep of inducible IFT88 KO mice. PAC, specifically between the theta-gamma bandwidths, has a well-established role in memory formation and is known to be disrupted in humans afflicted with mild cognitive impairment, Alzheimer’s, and Parkinson’s [25], [44][45]. Based off these data we can postulate that inducible IFT88 KO mice will have impaired memory formation, which has been recorded in preliminary behavioral experiments [46].…”
Section: Discussionmentioning
confidence: 91%
“…It was found that phase-amplitude coupling (PAC) between the theta and high-gamma frequencies was impaired in awake and in non-REM sleep of inducible IFT88 KO mice. PAC, specifically between the theta-gamma bandwidths, has a well-established role in memory formation and is known to be disrupted in humans afflicted with mild cognitive impairment, Alzheimer’s, and Parkinson’s [25], [44][45]. Based off these data we can postulate that inducible IFT88 KO mice will have impaired memory formation, which has been recorded in preliminary behavioral experiments [46].…”
Section: Discussionmentioning
confidence: 91%
“…Prior works on PAC in PD have focused on rest, but a recent study demonstrated that beta-gamma PAC was altered during transitions between different movement states (Gong et al, 2022). Our results show that PAC, at multiple frequency combinations, is directly related to MV, even in a single, overlearned task which would not necessarily involve switching between movement states.…”
Section: Discussionmentioning
confidence: 99%
“…The complete pipeline of analysis carried out is shown in Figure 2. Initially, the PAC value (See supplementary Material section 2) for each pair of the five standard EEG subbands-Delta (0.5-4 Hz), Theta (4-8 Hz), Alpha (8-16 Hz), Beta (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and Gamma (32-45 Hz)-was calculated to create a 2-dimensional representation of PAC values using TensorPAC [36], an open-source Python library for PAC investigation of neurophysiological data. Subsequently, we used the VGG-16 architecture [37] for transfer learning (called PACNET) to train a model to predict MV.…”
Section: Pacnetmentioning
confidence: 99%
See 1 more Smart Citation
“…To be noted, a number of theoretical theories and laboratory results has shown the significance of interactions between activities occurring at various frequencies, especially in processing and transmissing information. However, to find the exact relationship between different frequency bandwidth require methods different from the traditional way of processing information such as wavelet convolution or STFT, which always focus on the independent oscillatory activity and therefore very hard to show the relationship between different frequency bands and even across different neural nucleus, as shown in the figure2 [8]. The coupling between theta and gamma in the hippocampus of rodents is one of the most well-studied examples of cross-frequency coupling (CFC).…”
Section: The Theory Of Cross Frequency Couplingmentioning
confidence: 99%